Prospects for digital cooperation between Kazakhstan and South Korea in the field of public administration - Khamitova, Н.Е.; Belyalova, А.Е. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
This article examines the features of digital transformation in Kazakhstan and South Korea in the field of public administration. The importance of public administration in the implementation of digital transformation policy is undeniable. Due to government support and the initiative to create innovative technologies, the country's digital infrastructure is developing. The quality of human life and the effective work of all spheres has become dependent on the new digital environment. Consequently, every country strives to introduce new digital innovations into all sectors of the economy every year. Accordingly, scientific research on this topic is relevant. In the article, based on the method of analyzing statistical data from databases such as the World Bank, UN E-Government Survey 2022, International Telecommunication Union Surveys (ITU), IMD World Competitiveness Ranking reports 2023, INSEAD The Global Competitiveness Rankings 2022, comparative tables of two countries were compiled on the main areas of digitalization of public administration. A matrix was compiled using the game theory method, which examines the dominant cooperation between Kazakhstan and South Korea in the field of digital transformation. It is assumed that in the context of effective and stable mutual cooperation between countries in the field of digitalization, the role of public administration in a broad sense acquires a significant role for each of the governments.